Formal transformations in the design of the interior spaces (Journal of the College of Basic Education, 2024)
Talking about form and its transformations is not an easy matter, to the extent that this is related to the multiplicity and diversity of trends in form, starting from the historical-cultural connection among humans in particular and peoples and nations in general, all the way to contemporary formal interventions and their changes and their connection to various transformations, and this appears clearly in all human activities, including Designs of interior spaces, which arise in a field of complex relationships that in turn constitute the essence of interior design, and since the process of designing interior spaces in itself is an organized and complex mental process, aiming to create comprehensive formal connections, therefore it is useful to study this process with all its repercussions and the diversity of its formal transformations. That is, monitoring the transformations that occurred in the design process, so the researcher decided to choose the title of her research (Formal Transformations in the Design of Interior Spaces) to be a research topic that addresses the aspects of the design process in interior spaces. The research relied on the theoretical study of public interior spaces. The research was divided into three chapters. The first chapter included the research problem and its importance, as well as clarifying and defining the goal and limits, and defining the most important terms mentioned in it. As for the second chapter, it dealt with the theoretical framework, with three sections. The first section dealt with studying the concept of transformation, while the second section dealt with formal transformations according to modern schools, while the third section included applications of modernity and post-modernism for public interior spaces, and the third chapter was devoted to the results of applications of modernity. And postmodernism in public interior spaces. In light of the results and their discussion, conclusions were drawn and the research ends by presenting research recommendations and proposals related to the subject of the study.